Monomania : the flight from everyday life in literature and art - Van Zuylen, Marina (Cornell University Press, 2005)
'Monomania' explores the cultural prominence of the idée fixe in Western Europe during the 19th and 20th centuries. The author revives the term monomania to explore the therapeutic attributes of obsession.